Comparative Analysis of Location Management Schemes in Wireless ATM Networks - Usmani, Uzma (1999)
Mobility is the cornerstone of wireless networks. Supporting mobility requires some form of tracking to locate mobile terminals within the network. In the wireline ATM network, the terminal is fixed and the terminal is located by identifying the terminal and following the routing information provided at each switch along the path. As terminals become mobile, the path to the mobile becomes dynamic; the terminal and the path are no longer synonymous. Signalling traffic incurred in tracking mobile users and delivering enhanced services causes an additional load in the Wireless ATM (WArM) network. Efficient database and location management schemes are needed to meet the challenges from high density and mobility of users, and various service scenarios. In this thesis the three "natural" Location Management Strategies, i.e., Timer-Based, Location Area Based and Movement Based are studied and analysed for a W ATM network. The model used for depicting user motion and call arrival is Brownian motion with drift process and Poisson arrival process, respectively. The Timer-Based location management strategy is one in which the user updates its location periodically after an "optimum" interval of time. This optimum interval of time is based upon the user's mobility and call arrival characteristics and is therefore best suited for that particular mobile. In the Adaptive Location Area Based strategy, the user updates its location on each LA boundary crossing. The size of the LA changes according to the user' s mobility characteristics. The objective is to minimise the combined average signalling cost of both paging and registration for each individual mobile user such that the overall system-wide signalling cost for location tracking can be minimised.